Psychosocial issues and coping mechanisms of pregnant and postnatal women diagnosed with COVID-19: A qualitative study. (July 2022) - Kabwe, Jane Chanda; Lubeya, Mwansa Ketty; Phiri, Christabel Chigwe; Mulenga, Mubanga; Siulapwa, Ntungo; Kaonga, Patrick; Price, Joan T.; Phiri, Selia Ng'anjo; Jacobs, Choolwe
Objective: There is a paucity of data on the psychosocial issues and coping mechanisms among pregnant and postnatal women with COVID-19 infection. We, therefore, aimed to explore the psychosocial issues and coping mechanisms of pregnant and postnatal women diagnosed with COVID-19 at tertiary-level hospitals. Methods: This was a qualitative phenomenological study conducted in 2021 with a sample size of 16 women admitted at two referral hospitals serving as COVID-19 admission facilities for pregnant and postnatal women in Lusaka, Zambia. In-depth interviews were conducted via telephone to understand what these women experienced when diagnosed with COVID-19. All the interviews were audio-recorded and transcribed verbatim. Thematic analysis was conducted using the six steps approach to develop emerging themes. Results: Two major themes emerged: psychosocial issues and coping mechanisms. The primary psychosocial issues were worry and stigma. Women worried about infecting their unborn baby or neonate, being separated from the baby, the general safety of the baby, and the health of other family members. Women also worried about the attitude of health care providers and faced discrimination or stigma because of their infection. Thus, some coping mechanisms were developed that helped them, such as a positive attitude, keeping the disease secret, reliance on family members for support and using positive information from social media. Conclusion: This study provides unique insights into the psychosocial experiences of pregnant and postnatal women diagnosed with COVID-19. Women were particularly concerned about the unborn baby's well-being and discrimination. This study suggests the need for policy and clinical practice to consider the integration of effective mental health services into the provision of maternal health and COVID-19 services.